Pengaruh Pemahaman Teknologi Informasi, Kualitas Pendidikan, Lama Usaha dan Ukuran Usaha Terhadap Penerapan SAK ETAP pada Ekonomi Kreatif (Studi Kasus Pada UMKM di Kota Jambi) - Susfayetti Susfayetti; Affrizal Affrizal; Nela Safelia (Jurnal Akuntansi & Keuangan Unja, 2018)
This study aimed to the effect of understanding of Information Technology, the quality of the owner's education, the length of business, and the size of the business against the implementation of SAK ETAP on the Creative Economy of case studies on MSMEs in Jambi City. The benefit of this research was as an input to evaluate the entrepreneur of UMKM in Jambi regarding the importance of using good financial report and as further knowledge about SAK ETAP information. Methods of data collection were done through interview techniques and questionnaires to the owners of batik SMEs in Jambi city. Multiple Linear Regression was used as analyzer. There were three types of testing in hypothesis testing, namely Simultaneous Significance Test (Test Statistic F), Individual Parameter Significance Test (Test Statistic t) and Determination Coefficient Test (R2). Based on the results of hypothesis testing, it can be concluded that: (1) Understanding of Information Technology influenced the application of SAK ETAP, (2) The business owner's education background affected the application of SAK ETAP, (3) The age of business determined the application of SAK ETAP, (4) The size of the business had impact on the application of SAK ETAP, (6) Understanding of Information Technology, owner's educational background, length of business, and size of business were simultaneously influential to the application of SAK ETAP. Keywords: Quality of The Owner's Education, Understanding of Information Technology, Old Business, Business Size, SAK ETAP